1989
DOI: 10.1111/j.1471-4159.1989.tb07394.x
|View full text |Cite
|
Sign up to set email alerts
|

Separate Binding and Functional Sites for ω co‐Conotoxin and Nitrendipine Suggest Two Types of Calcium Channels in Bovine Chromaffin Cells

Abstract: Purified adrenomedullary plasma membranes contain two high-affinity binding sites for 125I-omega-conotoxin, with KD values of 7.4 and 364 pM and Bmax values of 237 and 1,222 fmol/mg of protein, respectively. Dissociation kinetics showed a biphasic component and a high stability of the toxin-receptor complex, with a t1/2 of 81.6 h for the slow dissociation component. Unlabeled omega-conotoxin inhibited the binding of the radioiodinated toxin, adjusting to a two-site model with Ki1 of 6.8 and Ki2 of 653 pM. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…nM Wheeler et al, 1994 Owen et al, 1989;Rosario et al, 1989 . Indeed, while several groups including ours have consistently emphasized the lack of effect of v-conotoxin GVIA 2q Ž in depolarization-evoked Ca influx this paper and Ballesta et al, 1989;Owen et al, 1989;Rosario et al, . 1989;Duarte et al, 1993a , others-using single cell w 2q x Ca measurements-have reported the occurrence of i cell-specific and variable inhibitory effects of the toxin Ž .…”
supporting
confidence: 51%
See 1 more Smart Citation
“…nM Wheeler et al, 1994 Owen et al, 1989;Rosario et al, 1989 . Indeed, while several groups including ours have consistently emphasized the lack of effect of v-conotoxin GVIA 2q Ž in depolarization-evoked Ca influx this paper and Ballesta et al, 1989;Owen et al, 1989;Rosario et al, . 1989;Duarte et al, 1993a , others-using single cell w 2q x Ca measurements-have reported the occurrence of i cell-specific and variable inhibitory effects of the toxin Ž .…”
supporting
confidence: 51%
“…observations . Furthermore, 1 mM is about 1000 times greater than the K for nitrendipine binding to bovine d Ž adrenomedullary membrane fragments Garcia et al, 1984;. Ballesta et al, 1989 .…”
Section: Qmentioning
confidence: 92%
“…As for the SVL action (Fig. IF) (Garcia et al 1984;Artalejo et al 1991), N-type (Ballesta et al 1989;Hans, Illes & Takeda, 1990;Artalejo, Perlman & Fox, 1992), P-type (Gandia, Albillos & Garcia, 1993a;Albillos, Garcia & Gandia, 1993;Artalejo et al 1994), and Q-type (Lopez et al 1994), contributing in different degrees to exocytosis.…”
Section: Characteristics Of the Soluble Vesicle Lysatementioning
confidence: 99%
“…In analogy to chromaffin cells, the N-channel in PC12 cells is not functional (shown in Fig, 1A). Chromaffin cells contain oCgTx binding sites [29,30] and w-CgTx-sensitive currents 131,321 but neither catecholamine secretion nor increase of [Ca2']i transients were antagonized by w-CgTx [33,34]. Fu~he~ore, synaptota~in, a small synaptic vesicleassociated protein which is involved in mediating transmitter release [35], is absolutely non-essential in the secretion process in PC12 cells [36].…”
Section: The L-type Ca2' Channel Expressed In Pc12 Cellsmentioning
confidence: 99%